What kind of Bauhaus is in our minds? - Szalay, Miklós (ARTCADIA, 2022)
The renaissance predecessors of the Bauhaus idea: regular bodies, utopias, and absolute human proportions. The social and technological conditions of the Bauhaus and its contemporary parallels: dodecaphony, futurism, anarchism, the Soviet republic. Attention! The style of one totalitarian idea – that of Russian constructivism – is dangerous and forbidden to the other totalitarian idea, notably, that of Nazism. Thought experiment: the touch of the function. Bauhaus today: overpriced Barcelona chair and cheap IKEA. Final reckoning: we may be able to draw the line at the Bauhaus from which we can clearly distinguish between design and “art.”